Skin cancer outcomes and risk factors in renal transplant recipients: Analysis of organ procurement and transplantation network data from 2000 to 2021 - Hao, Xiaowei; Lai, Wenhui; Xia, Xinze; Xu, Junnan; Wu, Yangyang; Lv, Chao; Meng, Qingyang; Lv, Kaikai; Huang, Shuai; Luo, Zhenjun; Dong, Jun; Yuan, Qing (Frontiers in Oncology, 2022)
Purpose: Posttransplant skin cancer is the most common malignancy after patients have undergone renal transplantation. Through comprehensive observation with large sample size nationwide, understanding the risk factors and outcome of posttransplant skin cancer will help to develop appropriate patient surveillance and disease prevention strategies. Materials and Methods: This retrospective population-based cohort study was based on Organ Procurement and Transplantation Network data released in March 2021. The characteristics and outcome, including the patient and graft survival of recipients were compared. Risk factors for posttransplant skin cancer, cancer onset momentum, and mortality were determined. Results: A total of 199 564 renal transplant recipients were included. After renal transplantation, 7 334 (3.68%), 6 093 (3.05%), and 936 (0.47%) were diagnosed with squamous cell carcinoma, basal cell carcinoma, and melanoma, respectively. Skin cancer was the major cause of death (squamous cell carcinoma: 23.8%, basal cell carcinoma: 18%, melanoma: 41.6%). Five-year survival rates ranked from best to worst were basal cell carcinoma ([95% confidence interval, CI], 96.7 [96.3–97.2] %), squamous cell carcinoma (94.1 [93.5–94.6] %), melanoma (89.7 [87.7–91.6] %), and cancer-free (87.4 [87.2–87.5] %), (P<.001 for all except melanoma vs. cancer-free, P=.534). Regarding graft survival, death-censored graft survival, posttransplant skin cancer, and melanoma were significantly better than the cancer-free group (P<.001). Independent risk factors for developing posttransplant skin cancer included older age, male sex, Caucasian race, pretransplant malignancy, polycystic kidney disease-induced end-stage renal disease (ESRD), retransplantation, private health insurance, T-cell depletion induction, and tacrolimus/mycophenolic acid use. Caucasian race and pretransplant malignancy were independent risk factors for posttransplant skin cancer onset momentum. Male sex, Caucasian race, pretransplant malignancy, hypertension-, or diabetes- induced ESRD, retransplantation, diabetes history, deceased donor, cyclosporin, and mTOR inhibitor use were independent risk factors for posttransplant skin cancer mortality. Conclusions: Although posttransplant skin cancer is a major cause of recipient death, information regarding its impact on patient and graft survival is limited. Given the differences regarding risk factors for posttransplant skin cancer incidence, onset momentum and mortality, personalized approaches to screening may be appropriate to address the complex issues encountered by kidney transplant recipients.